2018
DOI: 10.4316/bf.2018.015
|View full text |Cite
|
Sign up to set email alerts
|

Riscul la incendii în pădurile din România: cartare și metode de evaluare

Abstract: The paper presents results of a risk analysis of forest fires at county level, based on published statistical data of period 1976-2000 ("Health condition of the forests în Romania") and different methodologies to assess the fire risk of forest stands using the Standardized Precipitation Index (SPI) and a methodology integrating GIS techniques. The global fire risk model, based on the cumulated ranks on the analyzed period, indicated a very higher risk for forests in the southwest and southeast of Romania (the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…and Scots pine (Pinus sylvestris L.) which are mainly represented by plantations in Romania ( Bouriaud & Popa, 2009). In line with global climate trends, drought is considered an important threat for the Romanian forests (Lindner et al, 2010), high drought-related tree decline and mortality events being already observed (Barbu & Popa, 2001;Sidor et al, 2019;Curiel Yuste et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…and Scots pine (Pinus sylvestris L.) which are mainly represented by plantations in Romania ( Bouriaud & Popa, 2009). In line with global climate trends, drought is considered an important threat for the Romanian forests (Lindner et al, 2010), high drought-related tree decline and mortality events being already observed (Barbu & Popa, 2001;Sidor et al, 2019;Curiel Yuste et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…Levanič et al (2013) concluded that the number of extreme events was variable over time, and although the frequency occurrence of these events in the 20 th century was similar to the 18 th century, a considerable increase has been observed recently. Climate prediction models indicate that the southern and eastern parts of Romania are the most vulnerable regions to drought (Barbu & Popa, 2004apud Cleary et al, 2019.…”
Section: Current Warm Period (Cwp)mentioning
confidence: 99%